Antimicrobial susceptibility pattern of Methicillin-resistant Staphylococcus aureus in a tertiary care Hospital - Aqsa Aslam; Wajiha Mahjabeen; Muhammad Zia ul Rehman; Sana Qanber Abbasi; Nazish Babar; Huzaifa Saleem (Journal of University Medical & Dental College, 2022)
Background & Objective: Methicillin-resistant Staphylococcus aureus (MRSA) has become a major therapeutic issue across the world. The current study is designed to evaluate the trends in the susceptibility pattern of MRSA strains isolated from various clinical samples in a tertiary care hospital in Islamabad. The antimicrobial susceptibility pattern will not only add data but will also guide us about treatment options for MRSA infection. Methodology: This study was done in the Microbiology laboratory of Dr. Akbar Niazi Teaching Hospital, Islamabad after approval from the institutional ethical committee from May 2021 to December 2021. It was a descriptive cross-sectional study in which 155 clinical samples which revealed growth of Staphylococcus aureus were included by nonprobability convenient sampling technique. The cefoxitin disk was used to detect methicillin susceptibility. The susceptibility pattern of MRSA strains was seen against various antibiotics. The data entry and analysis were done using the Statistical Package for the Social Sciences (SPSS) version 25. Results: Out of 155 isolates of Staphylococcus aureus, 90(58.1%) isolates were MRSA. All the MRSA strains were sensitive to linezolid and vancomycin. The majority of the strains were sensitive to minocycline (71.1%), gentamycin (70%), and clindamycin (68.9%). The strains showed a relatively lower degree of sensitivity to other antimicrobials: trimethoprim/sulfamethoxazole (20%), ciprofloxacin (25.6%), levofloxacin (31.1%), and erythromycin (24.4%). There were only 2 MRSA strains isolated from urine samples which were sensitive to nitrofurantoin. Conclusion: There is a very high prevalence of MRSA in our setup. The majority of isolates are also resistant to macrolides, trimethoprim-sulfamethoxazole, and fluoroquinolones. Fortunately, all the MRSA strains are sensitive to vancomycin and linezolid.